Analyzing datasets under Instance Space Analysis framework: extension and exploration of hardness embeddings - Rodrigues, Diogo B.; Barros, Lucas R. R.; Queiroz, Alfredo A. A. E. de; Lorena, Ana C. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
In Machine Learning (ML), no single algorithm consistently outperforms others across all datasets. Meta-Learning aims to address the challenge of choosing suitable ML algorithms for new tasks by leveraging relationships between dataset characteristics and algorithm performance. One framework that supports this process is Instance Space Analysis (ISA), which enables the visualization of algorithm performance and instance hardness in a two-dimensional space. This study expands the ISA framework for analyzing classification datasets and ML algorithms, making it more complete and enabling meaningful insights into the relationships between dataset characteristics and ML classification performance.